Testing the diagnostic value of the dorsal sac and other structures of the roof of the female genital chamber within the plant bugs genus Psallus Fieber (Hemiptera, Heteroptera, Miridae, Phylinae) - Pluot-Sigwalt, Dominique; Matocq, Armand (Zootaxa, 2017)
The roof (dorsal wall) of the female genital chamber (bursa copulatrix) was compared in 31 species representing six subgenera of the taxonomically difficult genus Psallus Fieber, 1858. This investigation tested the potential value of different elements of the dorsal wall (dorsal sac, sclerotized rings, spermathecal gland, lateral oviducts, and infolding of the lateral margins), anticipating diagnostic characters and phylogenetic information for a genus in need of revision. The dorsal sac, a very variable membranous pouch differentiated from the vaginal wall, appears highly informative in providing reliable diagnostic characters at species level; to some extent it may also reveal related species. At subgenus or genus level, the dorsal sac must be examined with other equally informative structures of the roof. In some cases, strong evidence is provided by these structures aiding the recognition of related and unrelated species. The subgenus Pityopsallus Wagner forms a homogenous species-group which does not seems closely related to Psallus s.l. and should be raised to generic status as already proposed by several authors. The subgenus Hylopsallus Wagner appears to gather several species united by at least one synapomorphy after removing unrelated species such as P. (Hylopsallus) callunae Reuter. Also, it is clear that Psallus pardalis Seidenstücker and Psallus jungaricus Vinokurov & Luo should be excluded from Psallus. One or several characters in the roof of some phyline species (Atractotomus Fieber, Campylomma Reuter, Europiella Reuter, Phoenicocoris Reuter, Plagiognathus Fieber, Phylus Hahn, Sthenarus Fieber) appear to be distinct from those of Psallus species.